2015
DOI: 10.1016/j.puhe.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of habitual physical activity and organized sports in German primary school children

Abstract: In this study, a multiplicity of independent correlates of PA and sports participation, which require a broad approach to promote an active lifestyle, have been considered. Understanding these factors might support the development of effective health-promoting interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
4
16
1
1
Order By: Relevance
“…To our best knowledge, no study has investigated all of these activity‐related behaviors within a single adolescent sample, although Vella et al also found that higher levels of OSP were associated with increased likelihood of complying with physical activity guidelines among Australian adolescents and Mäkelä et al found a higher proportion of Finnish youth reaching the physical activity guidelines among those participating in organized sport (24.3%) compared to non‐participants (14.5%). Although the association between OSP and active transportation is an understudied area, a recent study among children found a positive association between OSP and active transportation to school, which is consistent with our results. Interestingly, a Danish study indicated that OSP was associated with increases of 5‐20 minutes in daily moderate‐to‐vigorous physical activity and 3‐ to 15‐fold increased odds of meeting recommended physical activity guidelines .…”
Section: Discussionsupporting
confidence: 92%
“…To our best knowledge, no study has investigated all of these activity‐related behaviors within a single adolescent sample, although Vella et al also found that higher levels of OSP were associated with increased likelihood of complying with physical activity guidelines among Australian adolescents and Mäkelä et al found a higher proportion of Finnish youth reaching the physical activity guidelines among those participating in organized sport (24.3%) compared to non‐participants (14.5%). Although the association between OSP and active transportation is an understudied area, a recent study among children found a positive association between OSP and active transportation to school, which is consistent with our results. Interestingly, a Danish study indicated that OSP was associated with increases of 5‐20 minutes in daily moderate‐to‐vigorous physical activity and 3‐ to 15‐fold increased odds of meeting recommended physical activity guidelines .…”
Section: Discussionsupporting
confidence: 92%
“…With respect to overweight/obesity status, the present data are in line with other studies in developed countries and at national and local levels . In regard to participation in organized sports, only approximately one‐half of children completed >120 min per week, in line with previous results . Regarding ETS exposure, the present proportion of exposed children was slightly lower than that calculated in a previous study in the same areas for 2007–2009 .…”
Section: Discussionsupporting
confidence: 91%
“…In line with our results, no differences were found between children with different weight status in previous studies during PE classes 26 or SR time. 5,26 However, the study of Kobel et al 46 with German schoolchildren detected higher levels of habitual MVPA in overweight than nonoverweight students. The study by Hohepa et al 7 with New Zealand adolescents also found that those who were classified as overweight/obese were more likely to be active than the normal weight adolescents.…”
Section: Discussionmentioning
confidence: 96%